Macroscopic lymphovascular invasion visualized on mammogram and magnetic resonance imaging: Initially misidentified as ductal carcinoma in situ but properly diagnosed by immunohistochemistry. (19th April 2017) - Sanders, Linda M; Dardik, Michael; Modi, Lopa; Sanders, Alison Esteva; Schaefer, Sarah S; Litvak, Anya
Objectives: Lymphovascular invasion (LVI) is a pathologic, microscopic finding associated with invasive cancer, and is a poor prognostic indicator, but has no reported imaging findings. This report presents the first documented case of LVI with seen by imaging. Linear branching microcalcifications were identified on mammography and clumped enhancement was noted on MRI, both imaging findings that are highly predictive of ductal carcinoma in situ (DCIS). Methods: Ultrasound guided core biopsy of the dominant mass was performed, confirming invasive ductal malignancy. Stereotactic biopsy performed on the microcalcifications was initially interpreted by pathology as DCIS. Results: Patient underwent mastectomy. Pathologic evaluation of the surgical specimen confirmed the invasive ductal malignancy. Microcalcifications were re-evaluated with immunohistochemistry (IHC) and re-classified as LVI. Radiology images and IHC stains are shown. Conclusion: This is the first report of LVI identified by imaging with findings that mimicked DCIS and initially mis-identified as DCIS by pathology as well. The implications of this overlap in radiologic appearance are discussed.